2010
DOI: 10.1029/2010ja015716
|View full text |Cite
|
Sign up to set email alerts
|

EMIC wave activity during geomagnetic storm and nonstorm periods: CRRES results

Abstract: [1] Electromagnetic ion cyclotron (EMIC) waves have been observed during geomagnetic storms and are thought to contribute to ring current and radiation belt particle loss during the main phase. Ground-based storm time studies alternatively observe the majority of storm time Pc1-2 pulsations during the recovery phase. In this study we look at the occurrences of EMIC waves during 119 storms occurring throughout the CRRES mission. The storms were defined using the Sym-H index. The storm was divided into three pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
236
7
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(266 citation statements)
references
References 73 publications
22
236
7
1
Order By: Relevance
“…Although EMIC waves have been intensively investigated [e.g, Kennel and Petschek, 1966;Young et al, 1981;Rauch and Roux, 1982;Roux et al, 1982;Anderson et al, 1996;Fraser and Nguyen, 2001;Halford et al, 2010;Pickett et al, 2010;Zhang et al, 2010Zhang et al, , 2011Min et al, 2012;Allen et al, 2013;Lin et al, 2014], plasma properties relevant to EMIC wave excitation have not been fully understood in the magnetosphere due to the wide spatial extent of EMIC wave generation and propagation. For example, Lin et al [2014] recently found that the correlation of positive A hp events, EMIC instability threshold (Σ h > S h ), and EMIC waves observed by the polar-orbiting Cluster spacecraft is low.…”
Section: Discussionmentioning
confidence: 99%
“…Although EMIC waves have been intensively investigated [e.g, Kennel and Petschek, 1966;Young et al, 1981;Rauch and Roux, 1982;Roux et al, 1982;Anderson et al, 1996;Fraser and Nguyen, 2001;Halford et al, 2010;Pickett et al, 2010;Zhang et al, 2010Zhang et al, , 2011Min et al, 2012;Allen et al, 2013;Lin et al, 2014], plasma properties relevant to EMIC wave excitation have not been fully understood in the magnetosphere due to the wide spatial extent of EMIC wave generation and propagation. For example, Lin et al [2014] recently found that the correlation of positive A hp events, EMIC instability threshold (Σ h > S h ), and EMIC waves observed by the polar-orbiting Cluster spacecraft is low.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of the electron loss is not simply controlled by the wave intensity but crucially depends on the wave spectral distribution [Glauert and Horne, 2005], and a properly specified global distribution of the EMIC wave power spectral density (PSD) is needed to accurately describe wave-particle interactions on the global magnetospheric scale throughout the 10.1002/2014JA020032 different storm phases. However, despite a number of statistical and case studies of EMIC waves [e.g., Anderson et al, 1992aAnderson et al, , 1992bFraser et al, 2010;Halford et al, 2010;Clausen et al, 2011;Usanova et al, 2012;Min et al, 2012], there is still no reliable global and dynamic model of the EMIC wave PSD that could be incorporated in the model of relativistic electrons in the outer RB. Currently, the EMIC wave PSD is poorly specified in all models of the outer RB relativistic electrons.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors found higher occurrence during the recovery phase than during the main phase. Halford et al (2010) indeed found that the majority of EMIC waves occur during the main phase but most of the events were observed in the dusk-noon sector and relatively few were observed for MLT > 18 h, whereas there were no anomalous IB dispersions observed for MLT < 19 h. It is also unclear why higher energy IBs never exhibit anomalous dispersion (Fig. 5c).…”
Section: Discussionmentioning
confidence: 77%
“…There are many observations supporting a wave-scattering scenario. Mostly, these are magnetospheric and low-altitude observations of the EMIC wave activity in the inner magnetosphere region (Bräysy et al, 1998;Erlandson and Ukhorskiy, 2001;Halford et al, 2010). Gvozdevsky et al (1997) investigated the intense proton precipitation equatorward of the IB which were called LLPP (low-latitude proton precipitation).…”
Section: Discussionmentioning
confidence: 99%